A Strategy of "Self‐Isolated Enhanced Emission" to Achieve Highly Emissive Dual‐State Emission for Organic Luminescent Materials. Issue 41 (11th July 2018) - Xu, Yanzi; Ren, Lin; Dang, Dongfeng; Zhi, Ying; Wang, Xiaochi; Meng, Lingjie
Abstract: Currently, the commonly developed organic luminescent materials (OLMs) usually exhibit poor luminescent performance in aggregated solid states compared with their well‐dissolved solution states, making it a tough goal to achieve the highly emissive dual‐state emission. To overcome this limitation, a "self‐isolated enhanced emission" (SIEE) strategy through flexible alkyl chains to suppress the emission‐quenched π–π stacking in solids is proposed here and, based on this guideline, remarkable emission efficiency with photoluminescence quantum yields up to 99.72 % in solution and 77.46 % in the solid state are achieved for the SIEE constructed DBBT‐C8, which is then successfully used in solid‐state displays and data encryption. Abstract : A self‐isolated enhanced emission (SIEE) strategy through flexible alkyl chains is proposed to suppress and prevent the emission‐quenched π–π stacking in aggregated solid states. As observed, remarkable emission efficiency with quantum yields up to 99.72 % in solution and 77.46 % in solids are achieved for DBBT‐C8 (see figure).